Superstardom in Popular Music: Empirical Evidence - Hamlen, William A. (The Review of Economics and Statistics, 1991)
This paper offers empirical evidence which counters two opposing but frequently expressed views concerning the market for popular music. The first view is that the consumers of popular music have no recognition of or appreciation for "quality" or "ability" in singing. The second is that the market is an example of the "Superstar Phenomenon, " in the Marshall-Rosen sense, wherein small differences in ability are magnified into disproportional levels of success. Using an external measure of "voice quality, " provided by the literature on voice, the estimated elasticity of record sales to voice quality is found to be significantly greater than zero but less than one. Copyright 1991 by MIT Press.